2013
DOI: 10.1177/0273475313491576
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Assessment of the Businessweek, U.S. News & World Report, and Financial Times Rankings of Business Schools’ MBA Programs

Abstract: This research investigates the reliability and validity of three major publications' rankings of MBA programs. Each set of rankings showed reasonable consistency over time, both at the level of the overall rankings and for most of the facets from which the rankings are derived. Each set of rankings also showed some levels of convergent and discriminant validity, but each has room for improvement, particularly Businessweek, which relies heavily on subjective surveys of students and recruiters, and Financial Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In contrast, other studies find significant annual variability in the ranking position of some organizations (Piro & Sivertsen, 2016), especially for performance on specific attributes (Carter & Ruefli, 2006;Iacobucci, 2013). Such variation is attributed to statistical noise (e.g., Bookstein et al, 2010), changes in rankings criteria and methodology (e.g., Tofallis, 2012), and exogenous events (e.g., Piro & Sivertsen, 2016).…”
Section: Future Research Opportunitiesmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, other studies find significant annual variability in the ranking position of some organizations (Piro & Sivertsen, 2016), especially for performance on specific attributes (Carter & Ruefli, 2006;Iacobucci, 2013). Such variation is attributed to statistical noise (e.g., Bookstein et al, 2010), changes in rankings criteria and methodology (e.g., Tofallis, 2012), and exogenous events (e.g., Piro & Sivertsen, 2016).…”
Section: Future Research Opportunitiesmentioning
confidence: 92%
“…Some scholars take a different point of view, arguing that, with reasonable expectations, rankings can facilitate decision making, especially if they are designed as “multi-dimensional transparency tools” that factor in the multiplicity of stakeholder interests (Van Vught & Westerheijden, 2010). Researchers (e.g., Iacobucci, 2013; Robinson-García, Torres-Salinas, López-Cózar, & Herrera, 2014) suggest that stakeholder audiences are best served by multiple rankings and the recognition that some rankings are appropriate for short-term planning while others can inform medium- and long-term decision making (Hou et al, 2012).…”
Section: Rankings As Information Intermediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal equilibrium as the first proposition of university ranking has also been the primary finding of studies of American law schools (Espeland and Sauder ; Jones ; Sauder and Espeland ; Sauder and Lancaster ), schools of business (Iacobucci ), and schools of public policy and administration (Frederickson and Stazyk ). These findings are particularly relevant to the study of university rankings and ranking systems given the observed “halo effect,” in which the reputational assessments of individual programs or departments are conflated by the reputation of the university of a whole, leading, in some cases, to nonexistent professional schools at prestigious universities receiving high reputational assessments (Brooks ; Webster ).…”
Section: A Conceptual Framework Of University Rankingmentioning
confidence: 96%
“…The MBA degree has been shown to enable students to (a) obtain jobs, (b) earn higher salaries, and (c) succeed in subsequent job performance (Iacobucci, 2013). Attaching the MBA to your name can affect your hiring chances, your networking abilities, and your innovation skills (Mondalek & Rogers, 2013).…”
Section: Discussion Recommendations and Conclusionmentioning
confidence: 99%